2022
DOI: 10.46729/ijstm.v3i3.510
|View full text |Cite
|
Sign up to set email alerts
|

The BUAS BUAS LEAF UTILIZATION OF BUAS BUAS LEAF (Premna pubescens Blume) ETHANOL EXTRACT AS LIQUID SOAP WITH ANTI-BACTERIA ACTIVITY

Abstract: The buas buas (Premna pubescens Blume) plant is from the Lamiaceae family. The use of ethanol extract of buas buas leaf (Premna pubescens Blume) as soap is because soap is one of the health products needed by many people to maintain a healthy body. It is used as an antibacterial because buas buas leaves contain secondary metabolites that can be used as antibacterial.The Buas buas leaf Simplicia (Premna pubescens Blume) was extracted using 96% ethanol by maceration and concentrated with a rotary evaporator to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
4
0
4
Order By: Relevance
“…Selisih kedua volume air yang terdapat dalam bahan yang diperiksa. Kadar air dihitung dalam persen (Rafita et al, 2022).…”
Section: Penetapan Kadar Air Dengan Metode Azeotropiunclassified
“…Selisih kedua volume air yang terdapat dalam bahan yang diperiksa. Kadar air dihitung dalam persen (Rafita et al, 2022).…”
Section: Penetapan Kadar Air Dengan Metode Azeotropiunclassified
“…Hasil uji yang diperoleh menunjukkan terbentuknya busa setelah perlakuan, dan setelah diberikan 1 tetes HCl 2 N busa tidak hilang. Indikator terbentuknya busa tersebut menunjukkan adanya kandungan senyawa saponin (Rafita et al, 2022).…”
Section: Skrining Fitokimiaunclassified
“…The results of the characterization examination showed that the water content of simplicia was 8%. Check the water and ethanol soluble essence levels in simplicia powder to see the amount that can be extracted with water and ethanol solvents from simplicia [17].…”
Section: Simplicia Characterization Examinationmentioning
confidence: 99%